Ready-to-Wear, Ready-to-Work: A Century of Industry and Immigrants in Paris and New York - Steedman, Mercedes (Labour / Le Travail, 1998)
The article reviews the book, "Ready-to-Wear and Ready-to-Work: A Century of Industry and Immigrants in Paris and New York," by Nancy L. Green.